Non-classical properties and generation schemes of superposition of multiple-photon-added two-mode squeezed vacuum state - Dat, Tran Quang; Thang, Truong Minh; Duc, Truong Minh (Hue University Journal of Science: Natural Science, 2021)
In this paper, we study some non-classical properties and propose the generation schemes of the superposition of multiple-photon-added two-mode squeezed vacuum state (SMPA-TMSVS). Based on the Wigner function, we clarify that this state is a non-Gaussian state, while the original two-mode squeezed vacuum state (TMSVS) is a Gaussian state. Besides, the SMPA-TMSVS is sum squeezing, as well as difference squeezing. In particular, the manifestation of the sum squeezing and the difference squeezing in the SMPA-TMSVS becomes more pronounced when increasing parameters r and e. In addition, by exploiting the schemes of photon-added superposition in the usual order, we give some schemes that the SMPA-TMSVS can be generated with the higher-order photon-added superposition by using some optical devices.